2016
DOI: 10.1111/jgh.13379
|View full text |Cite|
|
Sign up to set email alerts
|

A phase 3, open‐label study of daclatasvir plus asunaprevir in Asian patients with chronic hepatitis C virus genotype 1b infection who are ineligible for or intolerant to interferon alfa therapies with or without ribavirin

Abstract: Background and Aim: Daclatasvir plus asunaprevir has demonstrated efficacy and safety in patients with chronic hepatitis C virus genotype 1b infection. This study focused on evaluating daclatasvir plus asunaprevir in interferon (±ribavirin)-ineligible or -intolerant Asian patients with genotype 1b infection from mainland China, Korea, and Taiwan. Methods: Interferon (±ribavirin)-ineligible and -intolerant patients with genotype 1b infection received daclatasvir 60 mg tablets once daily plus asunaprevir 100 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…From a total of 678 unique studies identified using the search strategy, we included nine trials in this meta‐analysis, including 1690 patients (fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…From a total of 678 unique studies identified using the search strategy, we included nine trials in this meta‐analysis, including 1690 patients (fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have evaluated DCV plus other DAAs and/or pegIFNα/RBV. DCV plus sofosbuvir (DCV+SOF) or asunaprevir (DCV+ASV) has achieved high sustained virologic response (SVR) rates in diverse and difficult‐to‐treat populations . Compared with studies of pegIFNα/RBV‐containing regimens, studies of DAA‐only regimens have enrolled patients with more advanced disease due to less restrictive clinical and laboratory criteria, and DCV+SOF has achieved high SVR rates in patients with human immunodeficiency virus (HIV) coinfection, decompensated cirrhosis and post‐liver transplant recurrence …”
Section: Introductionmentioning
confidence: 99%
“…The combination of DCV once‐daily plus ASV twice‐daily for 24 weeks has demonstrated high SVR rates in patients infected with the GT 1b subtype of GT 1 in a number of clinical studies, both globally and in East Asian countries where GT 1b infection is predominant . A bioavailability study to select the phase 3 formulation (AI447024) was conducted and, based on these data, a lipid‐based softgel capsule was selected.…”
mentioning
confidence: 99%